Graph-QL Responsibility Analysis at Integrated Competency Certification Test System Base on Web Service - Masdiyasa, I Gede Susrama; Budiwitjaksono, Gideon Setya; M, Hafidz Amarul; Sampurno, Ilham Ade Widya; Mandenni, Ni Made Ika Marini (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 11 No 2 (2020): Vol. 11, No. 2 August 2020, 2020)
Graph-QL (Query Language) is a new concept in the Application Programming Interface (API). Graph-QL was developed by Facebook which is implemented on the server-side. Although it is a query language, Graph-QL is not directly related to the database, in other words, Graph-QL is not limited to certain databases, either SQL or NoSQL. The position of Graph-QL is on the client and server-side that access an API. One of the objectives of developing this query language is to facilitate data communication between the backend and frontend / mobile applications. For this reason, this paper will examine the responsibility of Graph-QL in terms of response time and response size in the development of an integrated competency certification test system based on web service and compared with efficiency and flexibility using the REST API. From the test results, it was found that Graph-QL provided some advantages compare to REST API. It give more flexibility for the clients to access the data and solve the most typical problem that was over or under fetching cause by fixed data given by REST API endpoints.